Disiplin Dalam Pengendalian Emosi Anak Usia Dini - Alifia Nurfadila; Dewi Siti Aisyah; Lilis Karyawati (Peneliti.net, 2023)
The type of research used is ex post facto quantitative research subjects are students of group B RA Al-Fadlillah, totaling 20 children. This data collection technique is through observation and interviews with parents conducted by researchers, the discipline and emotional attitudes of children are not well developed in training discipline and emotions of early childhood, parents and teachers must work together in giving attention and affection to children. children so that they are comfortable and safe. And also must pay attention to the environmental and daily aspects of the child because it is very influential in the development of a child’s personality or in the application of discipline child. and families give attention and affection to children so that children feel comfortable and safe when expressing feelings. In order to make children become influential individuals in the family and community environment, in the development of discipline, children interacting with their environment also affects emotional maturity in children, children also need to be accustomed to always being positive in interacting with the family environment and community environment.